Eye-Tracking in Educational Practice: Investigating Visual Perception Underlying Teaching and Learning in the Classroom - Jarodzka, Halszka; Skuballa, Irene; Gruber, Hans (Educational psychology review, 2021)
Classrooms full of pupils can be very overwhelming, both for teachers and students, as well as for their joint interactions. It is thus crucial that both can distil the relevant information in this complex scenario and interpret it appropriately. This distilling and interpreting happen to a large extent via visual perception, which is the core focus of the current Special Issue. Six empirical studies present examples of how to capture visual perception in the complexity of a classroom lesson. These examples open up new avenues that go beyond studying perception in restricted and artificial laboratory scenarios: some using video recordings from authentic lessons to others studying actual classrooms. This movement towards more realistic scenarios allows to study the visual perception in classrooms from new perspectives, namely that of the teachers, the learners, and their interactions. This in turn enables to shed novel light onto well-established theoretical concepts, namely students’ engagement during actual lessons, teachers’ professional vision while teaching, and establishment of joint attention between teachers and students in a lesson. Additionally, one theoretical contribution provides the very first model of teachers’ cognitions during teaching in relation to their visual perception, which in turn will allow future research to move beyond explorations towards hypothesis testing. However, to fully thrive, this field of research has to address two crucial challenges: (i) the heterogeneity of its methodological approaches (e. g., varying age groups, subjects taught, lesson formats) and (ii) the recording and processing of personal data of many people (often minors). Hence, these new approaches bear not only new chances for insights but also new responsibilities for the researchers.